Enhancing the standards of professionalism dan education for student enterpreneurship and soft skills development in Universiti Putra Malaysia - Abdullah, Zulhamri; Sabran, Mohamad Shatar; Ramlan, Mohd Fauzi (2012)
The study seeks to examine the role of students enterpreneurship programs in improving the graduate employability and marketibility. There are great debates pertaining to the role of university in making a solid contribution to nation’s economy/commodity. Today’s business in public and private sectors is hampered by a shortage of skilled workers who should possess highly academic qualifications and excellent soft skills. With the rise of business complexity and uncertainty around the world, students have two choices to make either becoming an employer or be a highly competent and talented employee who is capable of make a difference in their organization. The focus of this paper is to determine the effectiveness of enterpreneurship and soft skills programs that are being embeded in enterpreneurship and co-curriculum courses run by the Centre of Enterpreneurship Innovation and Student Development (CEISED), Universiti Putra Malaysia in order to improve the levels of employability and competitiveness among graduates. We analyzed seven key dimensions of the soft skills: (1) communication skills, (2) leadership skills, (3) teamwork skills, (4) entrepreneurship skills, (5) professional ethics and moral, (6) lifelong learning and information management, and (7) critical thinking based on a Malaysian Soft Skills Index (MY3S). The findings showed that there is an increase improvement of enterprising and soft skills among students who have formally taken enterpreneurship and co-curriculum courses. Indeed, this study implies that the greater involvement of students in enterpreneurship and co-curriculum courses, the better opportunities for student to improve their professionalism emphasizing on the effectiveness of student development services.